Primer for Space Cooling - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2020)
Developed in the context of the rapidly growing demand for space cooling and the critical need for access to affordable space cooling solutions, this primer aims to introduce a broad audience to the topic of space cooling and its key considerations, and to help initiate and advance sustainable space cooling into policy discussions and investment considerations in developing countries. The global energy use for space cooling is projected to grow three-fold between 2016 and 2050, with a majority of this growth occurring in developing countries. While the growing need for space cooling is in alignment with the developmental needs of countries, this growth must be addressed with carefully designed strategies and solutions to avoid severe economic, power system, and environmental impacts. Underscoring an integrative approach to space cooling, the primer provides with an overview of strategies that reduce the cooling loads of buildings by applying building efficiency measures that enhance thermal performance, serve the cooling load as efficiently as possible through appropriate choice of cooling solution and utilization of most efficient cooling equipment available, and optimize the performance of cooling through their operation. Discussing the barriers to implement sustainable space cooling, the primer also presents demonstrated space cooling intervention strategies that can help overcome these barriers, with over 100 real-world examples and implementation considerations included in the Compendium.